The Effect of Loan to Deposit Ratio and Growth Opportunity on Return on Asset in Banking Companies in 2019-2022 - Faizah Shofiyah Larasati R; Usep Syaipudin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the contribution of loan to deposit ratio and growth opportunity to the condition of banking financial performance. The population of this study is banking companies. The total sample of this study includes 180 samples from 45 companies for a 4-year research period. The research variables used are loan to deposit ratio, growth opportunity, return on assets, and size. The analysis technique used multinomial logistic regression analysis. The results showed that loan to deposit ratio is able to positively effect on return on assets, while growth opportunity has not been able to effect on return on assets.